2018
DOI: 10.3390/nu10121873
|View full text |Cite
|
Sign up to set email alerts
|

New Protocol for Production of Reduced-Gluten Wheat Bread and Pasta and Clinical Effect in Patients with Irritable Bowel Syndrome: A randomised, Double-Blind, Cross-Over Study

Abstract: It has been suggested that sourdough fermented products have beneficial health effects. Fungal proteases and selected sourdough lactic acid bacteria were used to produce wheat bread and pasta with a reduced-gluten content (<50% of traditional products). Fermentable oligo-, di- and mono- saccharides and polyols and amylase/trypsin inhibitors were also evaluated. The sensorial features of new products were similar to traditional ones. The efficacy of these new products in reducing the severity of symptoms in Irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…The efficacy of these products (containing <50% gluten content) was tested in a randomized, double-blind, crossover-controlled trial of 24 patients with irritable bowel syndrome (IBS) (compared to traditional bread and pasta). We demonstrated that, while consuming bread and pasta with reduced gluten content, IBS patients had significant symptom improvement as measured by the visual analogue scale score (p = 0.042) (27).…”
Section: Probiotics and Wheat Deglutinationmentioning
confidence: 82%
“…The efficacy of these products (containing <50% gluten content) was tested in a randomized, double-blind, crossover-controlled trial of 24 patients with irritable bowel syndrome (IBS) (compared to traditional bread and pasta). We demonstrated that, while consuming bread and pasta with reduced gluten content, IBS patients had significant symptom improvement as measured by the visual analogue scale score (p = 0.042) (27).…”
Section: Probiotics and Wheat Deglutinationmentioning
confidence: 82%
“…Gastrointestinal symptoms after consumption of control bread or sourdough bread were not significantly different. In a randomized, double-blind, cross-over study, tolerance of pasta and bread fermented with lactobacilli and fungal proteases was compared but only one questionnaire showed a lower score for IBS patients [ 45 ]. In both studies [ 32 , 45 ], effective degradation or reduction of ATI were poorly documented and the study subjects were recruited from IBS patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized, double-blind, cross-over study, tolerance of pasta and bread fermented with lactobacilli and fungal proteases was compared but only one questionnaire showed a lower score for IBS patients [ 45 ]. In both studies [ 32 , 45 ], effective degradation or reduction of ATI were poorly documented and the study subjects were recruited from IBS patients. In IBS patients, effects of ATI degradation are confounded by reduced levels of fermentable oligo-, di-, mono-saccharides, and polyols (FODMAPs) in sourdough bread.…”
Section: Discussionmentioning
confidence: 99%
“…Gluten sensitivity symptoms disappear in people that follow a gluten free diet. Nevertheless, the threshold of gluten intake related to the adverse reaction in subjects affected by gluten sensitivity is still debated and it has not yet been precisely established [56]. People suffering from gluten sensitivity are commonly affected by irritable bowel syndrome (IBS), an intestinal disorder that causes abdominal pain, bloating, diarrhea, constipation, and gut microbiota unbalance [2].…”
Section: Cereal-based Sourdough In Pasta Makingmentioning
confidence: 99%
“…In a recent study, pasta with a reduced gluten content was produced using fermented semolina [56]. Gluten hydrolysis was carried out by sourdough fermentation using a pool of selected lactobacilli and fungal proteases [50].…”
Section: Cereal-based Sourdough In Pasta Makingmentioning
confidence: 99%